2011
DOI: 10.2174/2212797611104030212
|View full text |Cite
|
Sign up to set email alerts
|

Review of Active Vibration Isolation Strategies

Abstract: This paper reviews recent patented developments in active vibration isolation. First of all, the fundamental limitations of passive vibration isolations are established, to understand the motivations to introduce active control in vibration isolation. Then, the main different active strategies are presented using simple systems and compared. Finally, several specific issues are listed and briefly discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 23 publications
0
14
0
1
Order By: Relevance
“…For this, the stiffness value of the link between QF1 and the ground has been modified to k q ¼ 1e7N=m. This configuration corresponds typically to a big mass placed on a rubber layer in series with a piezoelectric actuator [23]. Figure 16 shows the transfer functions between the ground and the quadrupoles when the feedback control is turned off and on.…”
Section: B Active Isolationmentioning
confidence: 99%
“…For this, the stiffness value of the link between QF1 and the ground has been modified to k q ¼ 1e7N=m. This configuration corresponds typically to a big mass placed on a rubber layer in series with a piezoelectric actuator [23]. Figure 16 shows the transfer functions between the ground and the quadrupoles when the feedback control is turned off and on.…”
Section: B Active Isolationmentioning
confidence: 99%
“…Active isolators can perform at a higher level than passive isolators through the incorporation of an active component. Collette et al have reviewed several patented developments in the field of active vibration isolation [4]. ey demonstrated that active suspension does not suffer from the two fundamental trade-offs between the settling time caused by the direct excitation of payload and the transmissibility by the base excitation through the isolator which are inherently given to passive suspension design.…”
Section: Introductionmentioning
confidence: 99%
“…(iv) Stabilization and isolation of large instruments dedicated to extreme experimental physics, like gravitational wave interferometric detectors or future particle colliders. In these systems the immunity to environmental disturbances is obtained by actively cancelling the structural vibration measured by inertial sensors [15].…”
Section: Introductionmentioning
confidence: 99%